Microparticle-coated microneedle scaffolds for transdermal drug delivery - CESUR, SÜMEYYE; GÜNDÜZ, OĞUZHAN (My University, 2022)
Transdermal drug delivery system (TIDS), is a method in which drug release was provided through the skin. Microneedle is one of the tools of TIDS, which is placing micron-sized needles on the skin. Some 3D printers, such as Digital Light Processing (DLP) 3D printers, are useful tools to produce microneedles. TIDS can be strengthened by using materials sensitive to stimuli in order to provide drug release in a controlled manner. In this study, microneedle production was made using a DLP 3D printer. The microneedles were coated with electrically active silver nanoparticles and drug-loaded polylactic acid (PLA) microparticles using the electrospraying machine. Characterization tests were performed on the microneedles. A scanning electron microscope (SEM) to view the morphology of microneedles, a fourier transform infrared (FTIR) spectrometer to learn about its molecular structure, a tensile device was used to determine the tensile strength, a differential scanning calorimetry (DSC) device to detect its thermal properties, X-ray diffraction to determine the crystal structure, swelling and degradation tests were carried out. An electrically stimulated drug release test was performed on microneedles. Microneedles were tested on bacteria to determine their antimicrobial property. As a result, microneedles were successfully coated with PLA microparticles and permitted drug release. The study proves the usability of microneedles coated with microparticles in stimulated drug release.
Keywords: Sağlık Bilimleri; Mühendislik ve Teknoloji; Health Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Microneedle; Polylactic acid; microparticles; drug delivery